FAKTOR YANG MEMPENGARUHI KELUHAN MUSCULOSKELETAL DISORDERS (MSDs) PADA PEKERJA INFORMAL - Aulia Tjahayuningtyas (The Indonesian Journal of Occupational Safety and Health, 2019)
Musculoskeletal disorders (MSDs) is a disorder or damage to the joints, ligaments, muscles and other skeletal systems due to unnatural or awkward body position especially if carried on for a long duration. Complaints of MSDs are influenced by internal factors (age, work durration, exercise habits, and body mass index) and external factors (work position and workload). The purpose of this study was to analyze the relationship between internal and external factors on complaints of MSDs to workers in the informal sector. The research design was crossectional approach. Data was analyzed by chi-square. The results of this study to 38 workers show that age (p = 0.102), exercise habits (p = 0.297), BMI (p = 0.332) and work positions (p = 0.864) have no relation to MSDs complaints while work durration (p = 0.019) and energy expenditure (p = 0.000) has a relationship with MSDs complaints. The conclusions of this research was that workload durration and cooking workload have a relationship with the complaints of MSDs in informal workers. Based on the level of MSDs complaint, mostly, workers felt the complaint on the right hand wrist (86%) and right foot (68%). It is recommended to informal workers to stretch the muscles on the sidelines of doing the work so that MSDs complaints can be minimized.Keywords: cooking work load, informal worker, manufacturing industry of tofu, subjective complaint of MSDs